2021
DOI: 10.1101/gr.275348.121
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying full-length circular RNAs in cancer

Abstract: Circular RNAs (circRNAs) are abundantly expressed in cancer. Their resistance to exonucleases enables them to have potentially stable interactions with different types of biomolecules. Alternative splicing can create different circRNA isoforms that have different sequences and unequal interaction potentials. The study of circRNA function thus requires knowledge of complete circRNA sequences. Here we describe psirc, a method that can identify full-length circRNA isoforms and quantify their expression levels fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…The expression level of each circRNA was identified using the psirc-quant program [ 73 ] based on likelihood maximization by mapping the rRNA-depleted reads to the integrated circRNAs. The TPM was calculated to normalize the expression level of each circRNA by the following formula: …”
Section: Methodsmentioning
confidence: 99%
“…The expression level of each circRNA was identified using the psirc-quant program [ 73 ] based on likelihood maximization by mapping the rRNA-depleted reads to the integrated circRNAs. The TPM was calculated to normalize the expression level of each circRNA by the following formula: …”
Section: Methodsmentioning
confidence: 99%
“…For quantifying expression values, we use psirc [20], which in turn employs kallisto [34] considering both linear and circular transcripts in the expectation-maximization step to yield comparable expression values. If the data has been sampled from different conditions (e.g., case and control), the quantified linear transcripts and circRNAs can be used to perform a differential expression analysis using DESeq2 [33].…”
Section: Pipeline Architecturementioning
confidence: 99%
“…Identification of circRNAs relies on the detection of back-splicing junctions (BSJ) among the unmapped reads, which allows for the estimation of circRNA abundance. By focusing on the back-splicing junction alone, the expression of circRNAs in relation to their linear counterparts is typically underestimated [20]. Several approaches for circRNA analysis have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…CIRI-full (Y. and CircAST (Wu et al, 2019) first locate the back-splicing junction positions suggested by other BSJ methods such as CIRI2 and perform local reads assembly to obtain full-length circRNAs. In 2021, psirc was published (Yu et al, 2021) with similar features to quantify full-length circRNAs while emphasizing application potentials in cancer samples.…”
Section: High-throughput Approaches To Characterize Circrnas In Full-...mentioning
confidence: 99%